2003
DOI: 10.1080/1363849031000095288
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of curvature progression in idiopathic scoliosis patients treated with scoliosis in-patient rehabilitation (SIR): an age- and sex-matched controlled study

Abstract: The goal of this study is to test the hypothesis that physiotherapy-based intervention can reduce incidence of progression in children with IS. Two independent patient groups matched by age and sex at diagnosis were analysed using the outcome parameter, incidence of progression (> or =5 degrees ). One group was untreated and the other received scoliosis in-patient rehabilitation (SIR). Incidence of progression in groups of untreated patients ranged from 1.5-fold (71.2% vs 46.7%) to 2.9-fold (55.8% vs 19.2%) hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
95
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(105 citation statements)
references
References 26 publications
2
95
0
6
Order By: Relevance
“…Weiss et al [18,27] reported on two independent patient groups with AIS matched by age and sex and measured the incidence of curve progression (C5°). The treatment group (115 patients) underwent a 4-6 week scoliosis in-patient rehabilitation (SIR) programme followed by at home daily exercises to maintain postural balance and the control group (107 patients) had no treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Weiss et al [18,27] reported on two independent patient groups with AIS matched by age and sex and measured the incidence of curve progression (C5°). The treatment group (115 patients) underwent a 4-6 week scoliosis in-patient rehabilitation (SIR) programme followed by at home daily exercises to maintain postural balance and the control group (107 patients) had no treatment.…”
Section: Discussionmentioning
confidence: 99%
“…None of the studies used standard functional outcome scores. Varied radiographic and clinical parameters were used with only 7 out of 12 studies reporting on changes in the Cobb angle [18,20,25,29,33,34,36]. However, the exact method used to measure the Cobb angle was not described and a nonstandardised method was used in one study [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, bracing as the cornerstone of this strategy remains controversial, as its effect is limited by non-compliance and potential negative psychosocial effects [2][3][4][5][6][7][8][9]. Intensive scoliosis-specific rehabilitation regimens might alter the curve's natural history, but these programmes are timeconsuming and lack evidence regarding their effectiveness [10][11][12]. Therefore, patients will often abandon these traditional approaches in favour of so-called ''holistic'' approaches, which are allegedly less harmful and more efficient alternatives.…”
Section: Introductionmentioning
confidence: 99%